The Safety and Regulatory Process for Amino Acids in Europe and the United States. Issue 12 (9th November 2016) - Roberts, Ashley
Abstract: The safety of long-term, high-dose amino acid consumption marketed as dietary supplements or functional or medical foods requires regulatory clearance in the European Union through the novel food process or through the Dietary Supplement Health and Education Act or the GRAS (Generally Recognized As Safe) route in the United States. The safety assessment of high daily doses of amino acids for bodybuilding or other health benefits is expected to require human studies to support tolerability and safety. The need for human studies is based on the fact that there is little or no evidence of toxicity from the conduct of animal toxicity studies and because standard animal testing would be inappropriate because of the large dosages required to provide a suitable margin of safety when extrapolating from animals to humans. Furthermore, the large dosages in animals required to provide a substantial margin of safety could lead to nutritional and physiologic imbalances, potentially confounding an amino acid safety assessment.